Chess tournament management system (scheduling module) - Lim, Jiin Kang (2005)
Scheduling problems has been a major problem in all fields. Each solution required a scheduling system to perform different task according to the need of that solution. Each solution involved different kind of resources and constraints, and some of these constraints are dynamic. Given the uncertainty of a schedule, it is impossible to produce a perfect solution to a problem. Producing a schedule for Chess Tournament has been considering a difficult task because of the constraints that need to be concern in the scheduling process are all dynamic. To fully utilize the resources available in a tournament are almost impossible. To solve the problem in utilizing the resources in a tournament, Genetic Algorithms approach has been used. Genetic Algorithms has been used as an approach in optimizing a solution.A scheduling system build using Genetic Algorithms is expected to produce a schedule that will utilize the usage of resources available.